IMPLEMENTASI VISI, MISI DAN PENDIDIKAN KARAKTER (AKHLAK) DI SMK PENERBANGAN AERO DIRGANTARA ISLAMIC VILLAGE - KABUPATEN TANGERANG - Sadarela Sadarela (LPPM Institut Nida El-Adabi, 2023)
This research is motivated by the difficulty in implementing the vision and mission of schools through Islamic education in realizing students with akhlak characteristics. The formulation of the problems in this study are 1) Description implement the school's vision and mission. 2) Deskription the obstacles in implementing the vision and mission of the school. 3) Deskription the level of success in the implementation of the school's vision and mission. through Islamic akhlak.